Phytochemical Profile and Biological Activity Evaluation of Zanthoxylum heterophyllum Leaves against Malaria - Ledoux, Allison; Maraetefau, Hinerava; Jansen, Olivia; Etienne, Delphine; Quetin-Leclercq, Joëlle; Clerc, Patricia; Smadja, Jacqueline; Frédérich, Michel (Planta Medica Letters, 2015)
The aim of this study was to evaluate the antiplasmodial properties of Zanthoxylum heterophyllum, an endemic plant from the Mascarene Islands. In vitro antiplasmodial activity of ethyl acetate and dichloromethane crude extracts obtained from leaf samples collected on Reunion Island was evaluated on the Plasmodium falciparum 3D7 chloroquine-sensitive strain using a colorimetric method. The major active compound was identified by chromatographic and spectroscopic methods. The best antiplasmodial activity was obtained for the ethyl acetate extract (15 µg/mL < IC50 < 50 µg/mL). The major compound was identified as a sanshool derivative, an alkylamide compound that has moderate antimalarial activity (IC50 = 11.3 µg/mL). This is the first report of the presence of a sanshool derivative in Z. heterophyllum. The moderate antiplasmodial activity of hydroxy-γ-isosanshool was demonstrated for the first time.
Keywords: Zanthoxylum heterophyllum; Rutaceae; malaria; antiplasmodial activitiy; Réunion Island; sanshool